2013
DOI: 10.1002/mc.22076
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AKT signaling promotes epithelial–mesenchymal transition and tumor growth in colorectal cancer cells

Abstract: Activation of the serine-threonine protein kinase AKT has emerged as a central feature of epithelial-mesenchymal transition (EMT), which is the initial step for metastasis in many cancer models, including colorectal cancer. The focus of our study was to dissect the role of AKT and its molecular regulation of EMT in colorectal cancer. HCT-116 colorectal cancer cells stably overexpressing AKT (AKT/HCT-116) showed significantly higher cell proliferation compared with vector-transfected cells (pCMV/HCT-116). Eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…In accordance to our study, it was reported that ERKTwist and PI3K/AKT-Twist pathway existed in many cancers and directly or indirectly promoted cell survival, motility, and invasion in EMT development [21][22][23]. Based on the cell Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance to our study, it was reported that ERKTwist and PI3K/AKT-Twist pathway existed in many cancers and directly or indirectly promoted cell survival, motility, and invasion in EMT development [21][22][23]. Based on the cell Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that the MAP kinase and Akt pathways play important roles in colon cancer cell invasion and migration (Tremblay et al 2006, Huynh et al 2010, Slattery et al 2012. The activation of Akt signaling promotes EMT and tumor growth in colon cancer cells (Suman et al 2014). In the present study, we showed that BDNF induced cell motility and upregulated VEGF expression via the induction of HO-1.…”
Section: Discussionsupporting
confidence: 56%
“…However, most CRC cases with PI3K mutations also carry mutations in KRAS 51 . The activated PI3K further activates AKT1 and AKT2, which then enhances tumor growth by promoting epithelial to mesenchymal transition (EMT) 52,53 . Loss-of-function mutations in PTEN, which is a tumor suppressor and an antagonist of the PI3K/AKT pathway, induce AKT-regulated metastasis in CRCs 54 .…”
Section: Mutational Landscape In Chromosomal Instabilitymentioning
confidence: 99%